An evaluation and exploration of Irish food-service businesses' uptake of and attitudes towards a voluntary government-led menu energy (calorie) labelling initiative. Issue 17 (16th August 2018) - Fitzgerald, Sarah; Gilgan, Lauri; McCarthy, Mary; Perry, Ivan J; Geaney, Fiona
Abstract: Objective: To investigate the uptake of and attitudes towards a voluntary government-led energy (calorie) menu labelling initiative in Ireland among a representative sample of food-service businesses and to inform further actions that may need to be undertaken to facilitate successful implementation. Design: A mixed-methods approach, incorporating a national telephone survey, structured observation visits and semi-structured interviews. Setting: Twenty-six counties in the Republic of Ireland. Subjects: A random selection of food-service businesses ( n 604) participated in the telephone survey. Businesses which indicated that they did display calories were selected to participate in structured observation visits ( n 42), along with a random sample ( n 38) of businesses that did not display calories. A purposive sample of thirteen food-service business owners who participated in the telephone survey participated in semi-structured interviews. Results: In the telephone survey, 7 % ( n 42) of food businesses reported displaying calories and the observation visits revealed that of these businesses, 10 % ( n 4) were not displaying calorie information. Three major themes emerged from the semi-structured interviews: uncertainty, impact on business and consumer nutrition knowledge. Participants expressed concerns regarding inaccuracies in the calorie information, cost and time implications, mistrust in the food-service industry and poor nutritional knowledge among consumers. These concerns impeded the implementing of calorie menu labelling. Conclusions: A multifactorial approach that incorporates guidance and support (training/tax incentives), practical assistance (user-friendly calorie calculation software), a reasonable legislative structure and a standardised monitoring system is needed to facilitate the successful implementation of calorie menu labelling.